The Making of Englishmen Debates on National Identity 1550-1650 - Larkin, Hilary (Brill, 2020)
Making the Englishmen: Debates on National Identity 1550-1650 asks how Englishmen defined themselves at a time of profound change and uncertainty. It will seek to contextualise the ways in which Englishness came to be construed as free, plain and unCatholic, and situate this construction as part of a larger attempt to create a narrative which would distinguish them from the rest of Europe. But all such attempts were fraught with anxiety and contestation. The normative ideals of Englishness were constantly being undermined, affronted and ignored. In the disarray characteristic of the post-Reformation era, there were constant fears that the Englishman was becoming both slavish and treacherous in political, cultural and religious ways. Englishness was under threat.